PENINGKATAN MOTIVASI BELAJAR SISWA MELALUI PENERAPAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) - Marini Marini; Abdur Rahman As’ari; Tjang Daniel Chandra (Graduate School of Universitas Negeri Malang, 2017)
The purpose of this study is to describe the learning process with the approach of Realistic Mathematics Education (RME), which can increase the motivation to learn mathematics student in materials Systems of Linear Equations in Two Variables on VIII-C students of SMP IT Ash-Shadhili. This research was a Classroom Action Research consisting of four stages, namely planning, action, observation and reflection. In the RME approach, teachers initiate learning by giving realistic problems. Students are asked to understand the problem and then solve it by discussing based on their knowledge and experience on teacher guidance. Students are then asked to discuss and compare answers through presentation activities during class discussions. Teachers motivate students to ask questions, give feedback or feedback. At the end of the learning the students are given the opportunity to deduce the material they have learned. The results showed that the RME approach learning can increase student motivation. This was proven by the percentage of observation results of students' learning motivation classically reached 83.33%, while the average percentage of observation results every meeting of two observers reached 80.37% in either category.Tujuan penelitian ini adalah untuk mendeskripsikan proses pembelajaran dengan pendekatan Realistic Mathematics Education (RME) yang dapat meningkatkan motivasi belajar matematika siswa pada materi Sistem Persamaan Linier Dua Variabel di kelas VIII-C SMP IT Asy-Syadzili. Penelitian ini merupakan Penelitian Tindakan Kelas yang terdiri atas empat tahapan, yaitu perencanaan, tindakan, pengamatan dan refleksi. Pada pendekatan RME, guru mengawali pembelajaran dengan memberikan masalah realistik. Siswa diminta untuk memahami masalah kemudian menyelesaikannya dengan cara berdiskusi berdasarkan pengetahuan dan pengalaman mereka atas bimbingan guru. Selanjutnya siswa diminta untuk mendiskusikan dan membandingkan jawaban melalui kegiatan presentasi pada saat diskusi kelas. Guru memotivasi siswa untuk berani bertanya, memberikan masukan atau tanggapan. Diakhir pembelajaran siswa diberi kesempatan untuk menyimpulkan materi yang telah dipelajari. Hasil penelitian menunjukkan bahwa pembelajaran dengan pendekatan RME dapat meningkatkan motivasi belajar siswa. Hal ini dibuktikan dengan persentase hasil observasi motivasi belajar siswa secara klasikal mencapai 83,33%, sedangkan rata-rata persentase hasil observasi setiap pertemuan dari dua orang observer mencapai 80,37% pada kategori baik.